Pengaruh Kecerdasan Emosional dan Motivasi Belajar Mahasiswa Virtual Selama Masa Pandemic Covid 19 Terhadap Pemahaman Akuntansi Mahasiswa - Asriani Asriani; Nur Diana; M. Cholid Mawardi (Universitas Islam Malang, 2023)
The study aims to examine the Effect of Emotional Intelligence and Learning Motivation of Virtual Students During the Covid 19 Pandemic on Students' Understanding of Accounting. This research includes quantitative research. In this study, the population studied was students majoring in Accounting at the Faculty of Economics and Business at the University of Islamic Malang, the sample used was purposive sampling, in which the criteria were determined by the researcher. This study used primary data and data collection techniques using questionnaires. The data analysis method used is multiple regression analysis. The results of this study are that simultaneously the variables emotional intelligence and learning motivation have an influence on students' understanding of accounting. Partially emotional intelligence has a positive effect on students' understanding of accounting. Partially learning motivation has a positive effect on students' understanding of accounting.Keywords: Emotional intelligence, student learning motivation, pandemic covid 19, understanding of accounting.